ANALISIS MINAT BELAJAR SISWA PADA PEMBELAJARAN IPS KELAS V DI SEKOLAH DASAR - Ni’mah Rahayu; Kanda Ruskandi; D. Wahyudin (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2021)
The spread of the COVID-19 outbreak has had a big impact on the lives of Indonesian, especially in sector education. The process of teaching and learning activities in Indonesia has to be carried out on a limited basis or remotely in accordance with the policy issued by the Minister of Education and Culture Number 4 of 2020 concerning the Implementation of Education in the Covid-19 Emergency Period. This study aims to determine student interest in learning and the factors that influence student interest in learning social studies on the subject history of national events during the colonial period in 5th grade SDN Purwamekar, Kab. Purwakarta, Prov. West Java. This research is a case study research type with a descriptive qualitative approach. Data collection techniques were carried out by questionnaires, interviews and documentation. The subjects of this study were 5th grade students and 1 teacher at SDN Purwamekar. The results showed that students' interest in social studies learning material history of national events during the colonial period was still quite sufficient because when learning it students did not feel happy, the materials was difficult to memorize and learning models and methods used by teachers were less attractive. The percentage results for the four subjects were : the largest percentage was obtained by 88% in the very good category, for the smallestpercentage obtained by 40% with the less category. good criteria with a percentage of 66% and a percentage of 62% with a good category. Factors that influence student learning interest are lack of enthusiasm for learning, different intelligence, the role of parents in educating and guiding children.